1998
DOI: 10.2307/172276
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Wife-Beating and Fetal and Infant Death: Impressions from a Survey in Rural India

Abstract: This report examines the linkages between wife-beating and one health-related consequence for women, their experience of fetal and infant mortality. Community-based data are used drawn from women surveyed in two culturally distinct sites of rural India: Uttar Pradesh in the north, in which gender relations are highly stratified, and Tamil Nadu in the south, in which they are more egalitarian. Results suggest that wife-beating is deeply entrenched, that attitudes uniformly justify wife-beating, and that few wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
172
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(190 citation statements)
references
References 7 publications
15
172
1
2
Order By: Relevance
“…28,29 They accepted DV as part of the marital life because of the perception of, fear of loss of the marital relationship and society's rejection. [29][30][31][32] The same perceptions had observed in the present study also. Women reported about evidence of relatively satisfied relationships too.…”
Section: Discussionsupporting
confidence: 90%
“…28,29 They accepted DV as part of the marital life because of the perception of, fear of loss of the marital relationship and society's rejection. [29][30][31][32] The same perceptions had observed in the present study also. Women reported about evidence of relatively satisfied relationships too.…”
Section: Discussionsupporting
confidence: 90%
“…Relation between maternal experience of violence, especially during pregnancy and morbidity like low birth weight of the baby, small size is well documented by existing studies [12,13,39]. Maternal experience of violence affects the survival status of the children too and this finding conforms to similar findings from other researches in Indian context [21,22,26,28]. Nutritional deficiency, small size of the baby at birth and lower birth weight are considered as two important predictors of death during the initial phase of life [32].…”
Section: Discussion Of Findingssupporting
confidence: 85%
“…A study conducted by Jejeebhoy [21], in rural Uttar Pradesh and Tamil Nadu, found that occurrence of child death below age five were more among mothers who have experienced violence because they had less autonomy, less decision making power and less access to resources. Another study in North India found similar associations between perinatal and neonatal mortality among children whose mothers had experienced violence [22].…”
Section: Introductionmentioning
confidence: 99%
“…Following the narrative provided in the earlier sections, the discussion focuses on the role of women's work status influencing the probability of experiencing violence. Most of the other variables have already been tested before in other studies on domestic violence (Vijayendra Rao 1997;Shireen Jejeebhoy 1998;Dallan F. Flake 2005;Pradeep Panda and Bina Agarwal 2005). Notes: Robust standard errors in parentheses.…”
Section: Instrumentmentioning
confidence: 99%